Effects of baicalein with memantine on aluminium chloride-induced neurotoxicity in Wistar rats - Jadhav, Ratnakar; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2023)
Alzheimer Disease is a progressive neurodegenerative disease. It is one of the most common forms of dementia accounting for 60-80% of people suffering from dementia. There are very few drugs which are approved for treatment of Alzheimer Disease. Baicalein, belonging to the flavone subclass of flavonoid, has been reported for neuroprotective effect by reducing oxidative stress, neuroinflammation, inhibiting AChE enzyme, reducing amyloid protein aggregation and toxicity. Memantine is one of the important drugs used for treatment of Alzheimer Disease. The present work was designed to study the effect of baicalein with memantine in aluminium chloride-induced neurotoxicity in Wistar rats. Aluminium chloride (100 mg/kg P.O.) was administered for 42 days in male Wistar rats to induce neurotoxicity. Baicalein (10 mg/kg) alone and combination of baicalein (5 mg/kg and 10 mg/kg) with of memantine (20 mg/kg) was administered for 42 days. Treatment of baicalein with memantine showed significant improvement in behavioural studies. The combination treatment decreased oxidative stress, β-amyloid plaque formation and increased the expression of brain-derived neurotrophic factor (BDNF) in brain. From the results, it can be concluded that treatment of baicalein with memantine could be beneficial for reducing the progression of neurodegeneration in rats.